Error Analysis of Students’ Speaking Class in Three-Months- Learning at Garlint English Course - Basri, Mohammad; Susie Chrismalia Garnida (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study analyzes linguistic errors in the oral utterances of 50 English as a Foreign Language (EFL) learners in speaking classes at Garlint English Course Pare who have studied for three months. Using a descriptive qualitative method and Error Analysis (EA) as the primary methodological framework, the study identified a total of 43 linguistic errors distributed significantly across noun phrase, word, and sentence levels. An in-depth observation of these patterns revealed that omission (7 cases at the word level) and misordering (6 cases at the noun phrase level, 5 cases at the sentence level) were the dominant error types most frequently committed by learners. These errors are primarily caused by intralingual transfer (such as L2 rule overgeneralization and developmental stages) and interlingual transfer from Bahasa Indonesia, for example, in the omission of the plural suffix (-s) on nouns. This research provides valuable insights for teachers and curriculum developers to design more targeted English language teaching strategies in intensive environments for the improvement of students' oral accuracy